2013
DOI: 10.1177/0300060513493692
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of probiotics and/or prebiotics for the prevention of eczema

Abstract: This meta-analysis found that probiotics or synbiotics may reduce the incidence of eczema in infants aged <2 years. Systemic sensitization did not change following probiotic administration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(38 citation statements)
references
References 46 publications
2
34
0
2
Order By: Relevance
“…Clinical trials have shown a wide range of beneficial effects of probiotics. Other probiotic intervention studies have also found at least a partial reduction in eczema [33,34] while others have found probiotics to have no effect [35][36][37][38]. Recent studies have also shown a beneficial effect of probiotics in the prevention of eczema.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical trials have shown a wide range of beneficial effects of probiotics. Other probiotic intervention studies have also found at least a partial reduction in eczema [33,34] while others have found probiotics to have no effect [35][36][37][38]. Recent studies have also shown a beneficial effect of probiotics in the prevention of eczema.…”
Section: Introductionmentioning
confidence: 99%
“…Nutrients 2017, 9,191 Phagocytic capacity outcomes were consistent among individual studies (SMD range: 0.60 to 1.01). Furthermore, each study reported statistically significant improvements in PMN phagocytic capacity with B. lactis HN019 relative to control.…”
Section: Study Selectionmentioning
confidence: 57%
“…Moreover, synbiotics are used in the treatment of hepatic conditions [189] and improve the absorption of calcium, magnesium, and phosphorus [190]. Danq et al (2013), in a meta-analysis, evaluated published studies on pro/prebiotics for eczema prevention, investigating bacterial strain efficacy and changes to the allergy status of the children involved. This meta-analysis found that probiotics or synbiotics may reduce the incidence of eczema in infants aged <2 years.…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…With the exception of atopic dermatitis, data from meta‐analyses have revealed insufficient evidence for probiotics in preventing the development of asthma, allergic rhinitis, or food allergy . With regard to preventing or reducing the severity of atopic dermatitis, there is evidence suggesting a benefit of probiotics, but this effect is variable and not consistent between studies . In one recent meta‐analysis examining 17 studies, results showed that when mothers were treated along with their infants with a probiotic, the infant had a significant reduction in RR for developing eczema compared to controls (RR, 0.78 [95%CI, 0.69‐0.89]; P < 0.001), particularly those supplemented with a mixture of probiotics (RR, 0.54 [95%CI, 0.43‐0.68]; P < 0.001) …”
Section: Evidence From Human Trials: Absent Evolving or Conclusive?mentioning
confidence: 99%